Entanglement creation by locally splitting a discordant state - Croal, Callum; Mišta, Ladislav; Chille, Vanessa; Peuntinger, Christian; Marquardt, Christoph; Leuchs, Gerd; Korolkova, Natalia (Optics InfoBase Conference Papers, 2014)
We introduce and experimentally implement counter-intuitive entanglement creation by locally splitting a classical mode that is part of a larger discordant state. Possible applications are quantum advantage in information encoding and assisted dense coding. © 2014 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05